2008
DOI: 10.1002/casp.924
|View full text |Cite
|
Sign up to set email alerts
|

Staying or returning: Pre‐migration influences on the migration process of German migrants to New Zealand

Abstract: Changes in migrants' backgrounds and societies sending and receiving migrants might increase adaptation issues and reduce retention. To enhance migrants' well-being/health and their likelihood of staying it is necessary to gain an understanding of psychological and social factors that contribute to resilience and adaptation. This paper presents findings from a qualitative study that investigated the experiences, interpretations and actions of German migrant couples to New Zealand throughout the whole migration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 14 publications
2
24
0
3
Order By: Relevance
“…This has also been noted in German migrants to New Zealand (Bürgelt, Morgan, & Pernice, 2008). Drivers in this study discussed 'self-induced' pressure to make the move a success, which is similar to previous findings (Tabor & Milfont, 2012).…”
Section: Discussionsupporting
confidence: 80%
“…This has also been noted in German migrants to New Zealand (Bürgelt, Morgan, & Pernice, 2008). Drivers in this study discussed 'self-induced' pressure to make the move a success, which is similar to previous findings (Tabor & Milfont, 2012).…”
Section: Discussionsupporting
confidence: 80%
“…Previous research on immigrant adjustment suggests that expectations of one's future migration may decrease uncertainty related to the decision to move (Black, 1992), as well as affect the formation of experiences (Ward et al., 2001, p. 204) and help behavioral adjustment (Bürgelt, Morgan, & Pernice, 2008) after migration. However, as pointed out by Szkudlarek (2010), most of the research on the relationship between premigration expectations and postmigration adaptation has been theoretically inconsistent and/or methodologically retrospective.…”
Section: From Expectations To Adaptationmentioning
confidence: 99%
“…The field survey method was employed in order to investigate the expectations and experiences of TAWs in Iceland. The questionnaire was constructed based on research done by Burgelt et al (2008). Furthermore, the survey was also based on findings in the qualitative phase of the research that authors of this article performed.…”
Section: Methodsmentioning
confidence: 99%
“…The focus on the relationship between expectations and their fulfillment has been researched extensively for years. Research by Burgelt, Morgan, and Pernice (2008) has shown that migrants who have limited firsthand information and who have inflated and high expectations about the new culture, tend to experience higher levels of disappointment, dissatisfaction and are more likely to return home prematurely than those who have more realistic information about the new culture. Furthermore, their study conducted on German migrants in New Zealand implies that migrants need resources such as migration counselling, language tuition by native speakers and information sources that give insights into what the migration process entails before they arrive in the new culture.…”
Section: Expectationsmentioning
confidence: 99%